PENGEMBANGANA MEDIA PEMBELAJARAN ENERGI KINETIK BERBASIS MIKROKONTROLER ARDOUNO UNO - Matsun Matsun; Boisandi Boisandi; Ira Nofita Sari; Soka Hadiati (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2021)
This research is a development research to develop learning media based on the Arduino Uno microcontroller in kinetic energy subjects with the help of ultrasonic sensors and load cells that are feasible and effective. The test subjects in this research and development consisted of material experts, media experts, physics subject teachers, and 12th grade students of MAN 1 Pontianak. The ADDIE development model used in this study consisted of five stages, namely: (1) the analysis phase, (2) the design phase, (3) the development phase, (4) the implementation phase, and (5) the evaluation phase. The results of material expert validation with an average score of 85%, and media expert validation with an average score of 87% indicate that the material and tool design developed is very feasible. Then, the teacher's response to physics lessons obtained a score of 83%, with very good criteria. The average score of student responses was obtained by a score of 89%, with very good criteria, which means that the learning media based on the Arduino Uno microcontroller in kinetic energy subjects with the help of ultrasonic sensors and load cells developed is easy to use by teachers and students.